Tooth tissue loss in locating mesiobuccal canal during selective retreatment using dynamic navigation system : an in vitro study = Pérdida de tejido dental en la localización del canal mesiovestibular durante el retratamiento endodóntico utilizando un sistema de navegación dinámica : un estudio in vitro - Sajjan, Girija S.
Selective root canal retreatment has demonstrated positive success, but the process is challenging because imprecision compromises the tooth's structural durability. As there is a lack of literature on selective retreatment using DNS, this in-vitro study was designed for comparative evaluation of tooth tissue loss and time taken in locating mesiobuccal (MB)canal using the dynamic navigation system (DNS; Navident, ClaroNav, Toronto, ON, Canada ) to the freehand (FH) method. The null hypothesis was that both methods would have similar tooth tissue loss and time required for the procedure. Twenty root canal-treated human mandibular molar teeth were mounted on Navident manikin. Using the Navident programme, the drilling path and depth were virtually designed using cone-beam computed tomographic (CBCT) scans. A minimal access cavity for locating the MB root was prepared with dynamic navigation in the DNS group and with freehand in the FH group. Volumetric tooth tissue loss was evaluated with the help of postoperative CBCT and On-demand software. Statistical analysis was done with an independent-sample T Test (p<0.05). The time taken for the procedure was recorded with a stopwatch. The tooth tissue loss was significantly less with the DNS group (35.83 mm³) compared to the FH group (52.84 mm³) with a P value of 0.001. The time taken for the DNS group was less with the DNS group (29.00 seconds) compared to the FH group (53.60 seconds) with statistical significance with a P value of 0.001. The DNS resulted in minimal tooth tissue loss with a shorter time compared to the FH group. This technique can be practised for predictable selective retreatment in endodontics.